Sipgi: an interactive pipeline for spectroscopic data reduction. Issue 2 (18th April 2022) - Gargiulo, A; Fumana, M; Bisogni, S; Franzetti, P; Cassarà, L P; Garilli, B; Scodeggio, M; Vietri, G
ABSTRACT: We present sipgi, a spectroscopic pipeline to reduce optical/near-infrared data from slit-based spectrographs. sipgi is a complete spectroscopic data reduction environment, which retains the high level of flexibility and accuracy typical of the standard 'by-hand' reduction methods but is characterized by a significantly higher level of efficiency. This is obtained by exploiting three main concepts: (i) the instrument model: at the core of the data reduction is an analytic description of the main calibration relations (e.g. spectra location and wavelength calibration) that can be easily checked and adjusted on data using a graphical tool; (ii) a built-in data organizer that classifies the data, together with a graphical interface that helps in providing the recipes with the correct input; (iii) the design and flexibility of the reduction recipes: The number of tasks required to perform a complete reduction is minimized, while preserving the possibility of verifying the accuracy of the main stages of data-reduction process with provided tools. The current version of sipgi manages data from the MODS and LUCI spectrographs mounted at the Large Binocular Telescope, and it is our plan to extend sipgi to support other through-slit spectrographs. Meanwhile, to allow using the same approach based on the instrument model with other instruments, we have developed SpectraPy, a spectrograph-independent python library working on through-slit spectra. In its current version, SpectraPy produces two-dimensional wavelength-calibrated spectra corrected by instrument distortions. The current release of sipgi and its documentation can be downloaded fromhttp://pandora.lambrate.inaf.it/sipgi/, while SpectraPy can be found at http://pandora.lambrate.inaf.it/SpectraPy/ .